Perkawinan Lintas Agama dalam Kajian Tafsir Formatif - M. Mu’allim (Qur'an and Hadith Academic Society, 2012)
This article discusses the issue of interreligious mariage in the formative era of Islam. It discusses the different opinions found in the time of the Prophet Muhammad, his Companions and his Followers. The primary sources of this article are the books of Hadith, the classical tafsirs which record the interpretation of the Qur’an in the Formative Period, and the book of history, such as Tabari’s Tarikh. This article concludes that there are two opinions in terms of interreligious marriage: those who opine the permissibility and those who opine the impermisibility